Síntese in situ pelo método Pechini e sinterização por métodos não convencionais de compósitos magnetoelétricos particulados - Perdomo, Claudia Patrícia Fernandez (Universidade Federal de São Carlos, 2015)
This thesis aimed the synthesis via in situ by Pechini method and the sintering by conventional and unconventional methods (microwave and spark-plasma) of particulates magnetoelectrics composites (ME) of ferroelectric systems 0,9Pb(Zn1/3Nb2/3O3)-0,1PbTiO3 (PZN-PT) and 0,675Pb(Mg1/3Nb2/3O3)- 0,325PbTiO3 (PMN-PT), combined with cobalt ferrite Fe2CoO4 (FCO), with 0,1≤x≤0,5 molar ratios of biphasic ferroelectric/ferromagnetic, aiming high densification, reduction in average grain size and microestructural controlling of constituent phases. The synthesis in situ by Pechini of both PZN-PT/FCO and PMN-PT/ FCO) composite systems was developed in an unprecedented way in this work, resulting successfully in two-phase systems without the presence of secondary phases, highly homogeneous distribution of constituent phases with an average size of nanometric particles and ensuring reproducibility of the method. The presence of FCO phase favored the 100% stabilizing of perovskite phase in PZN-PT system. Both (0,9PZN-0,1PT/FCO e PMN-0,325PT/FCO) systems, after conventional sintering, microwave and SPS showed no formation of secondary phases indicating that the stability of the perovskite phase in the PZN-PT and PMN-PT ferroelectrics phases were ensured. Unconventional sintering methods (microwave and SPS) allowed reach a percolation threshold in the compositions with high FCO content, beyond narrow distribution and lower average grain size favoring the obtaining of fine microstructures. All particulate composite systems sintering by the three techniques presented high resistivity values, even with the presence of high ferrite content which allowed its magnetoelectric characterization at low frequencies. Thus, the high degree of difficulty in getting the magnetoelectric composites, and the absence of studies of sintering microwave and spark-plasma and their effect on the physical and microstructural properties were the main motivation for the development of this work.
SYNTHESIS IN SITU BY PECHINI METHOD AND SINTERING BY UNCONVENTIONAL METHODS OF PARTICULATE MAGNETOELECTRIC COMPOSITE
Keywords: Síntese; Pechini; Sinterização; Microondas; Magnetoelétricos; CIENCIAS EXATAS E DA TERRA